The Role of Problem-based Learning Model in Enhancing Students’ Motivation and Physics Academic Achievement - Irawati, Een; Wati, Mustika; Khairunnisa, Yasmine; Mahtari, Saiyidah; Ulfah, Maria (KnE Social Sciences, 2025)
The teacher’s role in guiding and directing students to achieve desired academic achievement is crucial. By designing engaging learning activities, teachers optimize student involvement and presence, leading to increased motivation and improved academic achievement. At a senior high school in Banjarmasin, a research study using the problem-based learning (PBL) model was conducted to enhance motivation and academic achievement for 10th-grade students. The study focused on three areas: (1) lesson plan implementation, (2) students learning motivation, and (3) students’ academic achievement. Collaborative classroom action research was conducted in two cycles involving planning, implementation, observation, and reflection. Data were collected from 34 students through tests, observation, and documentation. The study findings indicated that: (1) Lesson plan implementation was improved from an average score of 3.34 (good) in cycle I to 3.84 (very good) in cycle II. (2) Students’ learning motivation increased from an average score of 2.29 (moderate) in the pre-cycle to 3.48 (very high) after the learning cycle. The N-gain score was 0.69 (moderate). (3) Students’ academic achievements had significantly improved, with the average pre-cycle score of 42.60 increasing to 83.44 after the learning cycle with the N-gain score of 0.70 (high). (4) Students’ responses to PBL were positive, with an average rating of 3.24, indicating a good category. In conclusion, implementation of the PBL model effectively enhanced students’ motivation and improved academic achievement of the 10th-grade students at the senior high school in Banjarmasin.